Absence of evidence or evidence of absence? A transfer and depletion study of Sudan I in eggs. (15th January 2018) - Piątkowska, Marta; Jedziniak, Piotr; Olejnik, Małgorzata; Żmudzki, Jan; Posyniak, Andrzej
Graphical abstract: Highlights: In house Sudan I contaminated red pepper was prepared. The pepper was used to prepare in-house contaminated-experimental animal feed. The feed was given to animals to investigate the Sudan I transfer to eggs. Sudan I concentrations in eggs were determined using LC-MS/MS method. Calculated transfer was very low what stands in the contrary to other authors suppositions. Abstract: Sudan I is a carcinogenic industrial azo-dye, forbidden for use in food. However, it has been detected in food on several occasions, such as in paprika, used in animal husbandry to enhance egg yolk colour. Therefore, an animal experiment was designed to simulate the transfer of Sudan I to eggs after its unintentional administration to laying hens. A group of laying hens (n = 18) received feed contaminated with Sudan I at the raising concentrations: 0.45 mg/kg, 4.97 mg/kg and 42.1 mg/kg. Residues of Sudan I were detected in egg yolks (0.29 ± 0.03 µg/kg, mean ± SD) only after the administration of the feed contaminated with the dye at the highest concentration. The determined concentrations were much lower than expected based on the compound's lipophilicity. In conclusion, the transfer of Sudan I to eggs was limited and strongly dependent on its concentration in feed.